Development of Balinese Ong Tea as a Probiotic Drink at Taruna Warmadewa Vocational School, Denpasar - Sudiarta, I Wayan; Semariyani, A.A. Made; Aditya, Ketut Tegar; Susilawati, Ni Wayan; Bira, Ela Tara Wini; Tiba, Andika Umbu (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Teh Ong, a fermented beverage rich in probiotic benefits, has enormous potential for further development. The purpose of community service is to develop a Balinese Teh Ong product as a probiotic drink at SMK Taruna Warmadewa Denpasar. This activity focuses on training and mentoring students majoring in hospitality and culinary arts to produce original Teh Ong. During implementation, the community service team guides the fermentation process for Teh Ong and ensures adherence to hygienic production operational standards. The mentoring aims to produce quality Teh Ong products and to foster students' entrepreneurial spirit and creativity. The result of this community service is the formation of a Teh Ong production group at the school, which can produce this probiotic drink independently. The resulting Teh Ong Original product boasts an authentic, refreshing taste and rich health benefits that support digestion. This success demonstrates that the development of locally innovative products can be an effective educational tool while also opening economic opportunities for the younger generation.Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 4: Quality Education